(untitled) (RIAF. International Journal of Physical Activity, 2025)
COVID-19 has caused profound and lasting changes in the dynamics of coexistence among university students, significantly affecting their mental health and academic performance. This study, focused on the University of Guayaquil, examines how these social and educational disruptions have impacted the academic and personal development of students in the post-pandemic context. The primary objective is to evaluate the impact of these changes in coexistence and social interaction dynamics, emphasizing their influence on students’ mental health, academic performance, and personal growth. A mixed-methods approach, combining quantitative and qualitative methods, was employed to enable a comprehensive understanding of the issue. The findings highlight that the pandemic has exacerbated stress and anxiety levels, underscoring the need for psychological programs and promoting resilience as a key factor in overcoming educational challenges. Additionally, the importance of optimizing virtual platforms, fostering support networks within the university community, and managing resources and physical spaces equitably was evident. The study concludes with a call to design personalized strategies and proactive policies that promote a resilient, cohesive, and adaptive educational environment to meet students’ needs in the post-pandemic context, thereby contributing to their emotional well-being and strengthening their academic formation.